PERFORMANCE IMPROVEMENT MODEL OF HUMAN RESOURCES (HR) THROUGH DIGITAL KNOWLEDGE SHARING - Marisa Giantari (UNISSULA, 2017)
This research is an explanatory research with a quantitative approach, which aims to test and analyze a research model where Human Capital and Social Capital predicts Human Resource Performance (HR) with Digital Knowledge Sharing as an intervening variable. The population in this study were 206 State Civil Apparatus (ASN) of 4 SKPD in the Rembang Regency Government. There were 102 ASN respondents who filled out and completed the research questionnaire. The collected data is processed using the SEM concept with the SmartPLS 3.0 Program, with the results of the study proving that the Variables of Human Capital, Social Capital and Digital Knowledge Sharing each have a significant positive effect on the Performance of Human Resources (HR), and Digital Knowledge Sharing partially mediates the influence of Social Capital on Human Resource Performance.Keywords : Human Capital, Social Capital, Digital Knowledge Sharing, and Human Resource Performance (HR)